Association Between Stress at Work and Onset of Menopause in Senior High Schools Women Teachers in Surakarta - Canda Arditya; Slamet Riyadi; Yusuf Ari Mashuri (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Bacground: Stress has been already known affecting hormonal axis. However, the association between stress and menopause is poorly understood. The study was aimed to determine the association between stress at work and the onset of menopause of the women teachers in Senior High Schools in Surakarta. Methods: This was an observational cross-sectional research using cross sectional design. The samplewas activewomenteachers who wereregularlyteaching inSenior High Schools at Surakarta who already had menstrual periods stop.Samplingwas done using a simple random sampling method with amount of sample 58womenteachers. The data of stress at work were obtained by International Stress Management Assosiation (ISMA) quistionare and the onset of menopause were obtained by interviews. The data were analyzed with unpairedt-test and Spearmancorrelationtest. Results: Stress at work was significantly correlated with the onset of menopause (r = -0.441; p = 0.009). Stress at work was found to be significantly associated with onset of menopause (p < 0.05). Conclusion: This research shows a significant correlation between work stress and the onset of menopause with negative direction and moderate strength. Keywords: menopause, stress at work